2014
DOI: 10.7860/jcdr/2014/8643.4109
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Trauma in Tertiary Care Centre in Dakshina Kannada District of Karnataka, India

Abstract: There has been an alarming increase in the number of trauma cases in the past decade. The target age group being the most productive one; it affects the economy directly . There is a need of urgent protective measures which are required for the benefit of the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
3
14
1
Order By: Relevance
“…Similarly in study done by Dsouza et al, Kalaiselvan et al and Ghimire A et al, injuries due to fall was being the most common mode of injury. 8,13,14 In the present study, association of alcohol consumption was seen in 663 (24.71%) patients with fall as mode of injury, 108 (15.2%) were those with RSA, whereas 8 patients were victims of assault. We could not screen for other intoxications attributable to drugs, due to nonavailability of regular testing at our institution.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Similarly in study done by Dsouza et al, Kalaiselvan et al and Ghimire A et al, injuries due to fall was being the most common mode of injury. 8,13,14 In the present study, association of alcohol consumption was seen in 663 (24.71%) patients with fall as mode of injury, 108 (15.2%) were those with RSA, whereas 8 patients were victims of assault. We could not screen for other intoxications attributable to drugs, due to nonavailability of regular testing at our institution.…”
Section: Discussionsupporting
confidence: 51%
“…Similar observation was made by Dsouza et al (M:F-2.3:1). 8 Samuel et al in their study on epidemiology of injuries at a tertiary care center in Malawi, found that males (75.7%) were predominating in total injured patients. 9 Several possible reasons for this have been suggested including greater number of vehicles driven by males and more participation in high risk activities, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our study are in agreement with other studies where majority of the RTA victims were males. [8][9][10][11][12][13][14] The difference may probably be due to the reason that males tend to travel more for work related and other purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were drawn by various authors. 15,16 This can be attributed to hurry to get back to home after completion of their work, poor light conditions and fatigue dur to all day long work.…”
Section: Discussionmentioning
confidence: 99%